The bioecology of snail vectors for schitosomiasis in Brazil - Barbosa Frederico S.; Barbosa Constança S. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
This paper describes the ecology of two species of Biomphalaria: B.glabrata and B. straminea. These species have been intensively studied in Brazil and in other countries since the 1950s. The literature in this area can be broadly subdivided into three categories, linked to three distinct historical periods: 1) an accumulated store of early studies carried out in the laboratory and in the field; 2) the development of quantitative ecological models; and 3) the development of an alternative methodology for breeding snails under seminatural conditions.